Efficacy and Safety of Standardized Protocol of CPAP Therapy for Full-Term Newborns in Delivery Room at Transient Tachypnea: Clinical Trial with Historical Control - Evgenii V. Shestak; Olga P. Kovtun; Olga L. Ksenofontova; Dmitry S. Dodrov (Вопросы современной педиатрии, 2022)
Background. Nowadays there is no consensus on the tactics and optimal protocol for Continuous Positive Airway Pressure (СРАР) at transient tachypnea of newborns (TTN) in delivery room.Objective. The aim of the study is to examine the efficacy and safety of standardized protocol of CPAP therapy for newborns with TTN in delivery room.Methods. The clinical study (implementation of standardized CPAP protocol) included full-term infants (gestational age — 37–41 weeks) with diagnosed TTN and CPAP therapy during first 60 minutes of life. Similar inclusion criteria were applied for the historical control group (born within previous year for whom CPAP was implemented according to “usual” protocol). Initiation of mononasal CPAP in main group was carried out when respiratory disorders were assessed according to Downes scale ≥ 3 points with control points at 20–40–60 minutes via the same scale, in control group at ≥ 4 points — for all cases, and according to the doctor's decision at 1–3 points. Mean airway pressure was maintained at 8 and 5–10 cm H2O, CPAP duration was 20–60 and 5–30 min, respectively. The major endpoints: the frequency of patient transfer from delivery room to intensive care unit or hospitalization to the neonatal pathology department, as well as total period of hospitalization. Moreover, frequency of invasive manipulations (intravenous catheterization, parenteral feeding), antibacterial therapy, cerebral injuries (cerebral ischemia, intracerebral hemorrhage), nasal passages injuries, pneumothorax (in the first 24 hours of life) were recorded during the entire hospitalization period.Results. 140 newborns with TTN were included in the clinical study, 30 were excluded from the study, specifically 13 due to violation of the CPAP protocol. The historical control group included 165 newborns. This groups were comparable for most baseline (before the start of CPAP) indicators except for maternal COVID-19 frequency during pregnancy and twin newborns frequency. This groups were comparable for most baseline (before the start of CPAP) indicators except for the frequency of maternal COVID-19 cases during pregnancy and the frequency of twin newborns. Hospitalization rate in intensive care units (18.2 versus 70.3%; p < 0.001) and neonatal pathology departments (31.8 versus 80.0%; p < 0.001), as well as total period of hospitalization (3 versus 10 days; p < 0.001) were lower in the standardized CPAP therapy group. Lower frequency of invasive manipulations, antibacterial therapy, and cerebral ischemia was recorded in this group. The safety of СРАР administration in delivery room was confirmed by the absence of nasal passages injuries in both groups, as well as comparable frequency of pneumothorax.Conclusion. The use of standardized CPAP protocol in delivery room for full-term newborns with TTN had higher rate of favorable hospitalization outcomes. Study limitations require validation of all the findings in independent studies.